Isolation, Screening and Evaluation of Biocontrol Potential of Rhizobacteria isolated from different agro-ecologies - Verma, Pooja; Chandra, Priyanka; Rai, Arvind Kumar; Basak, Nirmalendu; Sundha, Parul; Sehrawat, Anu; Dhuli, Pooja; Saharan, Baljeet Singh; Yadav, RK (Journal of Soil Salinity and Water Quality, 2023)
Bacteria are the most abundant class of microflora in the rhizosphere, followed by fungi, protozoa, algae, and actinomycetes. A group of beneficial bacteria thriving near the roots of plants are referred to as plant growth-promoting rhizobacteria (PGPR). Hence, the rhizospheric soil of monsoonal crops (rice, maize, sorghum, pearl millet, and pulses, such as urad and moong) and winter crops (wheat, wild oats, mustard and barley) were collected from different experimental fields of Karnal and Panipat for the isolation of rhizospheric bacteria. The dual culture plate method was used to assess the biocontrol potential of purified isolates against the fungal plant pathogens. A total of 184 isolated bacteria were subjected to qualitative screening for their biocontrol activity against seven test phytopathogenic fungi on PDA medium by single streak method. Most of the isolates demonstrated broad-spectrum activity in opposition to the test fungi. Out of the total 184 isolates, sixty-six isolates showed good biocontrol activity against the test phytopathogenic fungi and only 20 isolates exhibited desirable growth inhibition. The rhizobacteria demonstrated secretion of compounds showing biocontrol activity like siderophores, HCN, ammonia, hydrolytic enzymes like cellulase, chitinase etc. Thus, rhizobacteria can be utilized as a significant alternative to conventional farming practices for better and sustainable agricultural output, maintenance of food security, increased yields, effective plant protection, and the agro-economic industry